A review of anti-reflection and self-cleaning coatings on photovoltaic panels. (15th March 2020) - Sarkın, Ali Samet; Ekren, Nazmi; Sağlam, Şafak
Highlights: Anti-reflective and Self-cleaning coatings are applied for less reflection and more light transmittance. The most common methods are solgel + spin coating and solgel + dip coating methods. The most commonly used material in the literature is SiO2 and TiO2 . It has been found that the suitable coating coats are 2-3-4 with a high reflection index + low reflection index. Abstract: The production of electrical energy from solar energy through the photovoltaic method has become increasingly widespread throughout the world in the last 20 years. The photovoltaic energy system generates electricity depending on the amount of sunlight reaching the solar cell, and the amount of sunlight that reaches the solar cells in a solar panel decreases due to factors such as soil and organic dirt. At the same time, sunlight is refracted and reflected due to the reflective effect of the cover glass surface, even if the surface of the photovoltaic panel is clean. The remaining solar rays are broken and reach the solar cell. Decreasing sunlight also causes a decrease in electrical power output. Thus, to overcome these problems, photovoltaic solar cells and cover glass are coated with anti-reflective and self-cleaning coatings. As observed in this study, SiO2, MgF2, TiO2, Si3 N4, and ZrO2 materials are widely used in anti-reflection coatings. Common methods used are sol-gel + spin-coating or +dip-coating, sputtering, DC or RF magnetron, and electrospun methods. Regarding self-cleaning applications, fabricating superhydrophobic surfaces stands out among other methods. In self-cleaning applications, Al2 O3, TiO2, and Si3 N4 are the most suitable materials; the double- and triple-layer coatings yield successful results in terms of surface adhesion and durability. In multi-layer anti-reflection coatings, the reflectance was reduced in studies in which materials with low and high reflection indexes were applied and light transmittance was increased.